2019
DOI: 10.1371/journal.pone.0215572
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and determinants of acute respiratory infection among under-five children in Ethiopia: Ethiopian Demographic Health Survey 2016

Abstract: Background Childhood acute respiratory infection remains the commonest global cause of morbidity and mortality among under-five children. In Ethiopia, it remains the highest burden of the health care system. The problem varies in space and time, and exploring its spatial distribution has supreme importance for monitoring and designing effective intervention programs. Methods A two stage stratified cluster sampling technique was utilized along with the 2016 Ethiopian Dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 23 publications
(24 reference statements)
6
47
2
2
Order By: Relevance
“…The nding complies with a prior study in urban areas of Oromia region, Ethiopia [36]; in Wondo-Genet district, southern Ethiopia [19] and in Afghanistan [37]. This could be because of the few time the older children spend with their mothers in the house [37], and the higher number in younger children could be associated with the underdeveloped epithelial linings of the lungs and weaker immune system of younger children compared with the older counterparts [37][38][39].…”
Section: Discussionsupporting
confidence: 88%
“…The nding complies with a prior study in urban areas of Oromia region, Ethiopia [36]; in Wondo-Genet district, southern Ethiopia [19] and in Afghanistan [37]. This could be because of the few time the older children spend with their mothers in the house [37], and the higher number in younger children could be associated with the underdeveloped epithelial linings of the lungs and weaker immune system of younger children compared with the older counterparts [37][38][39].…”
Section: Discussionsupporting
confidence: 88%
“…The probable justification for the greater ARI symptoms proportion for rural children may be due to lack of access to medical care, low socio-economic standards in rural regions [47] and most risk factors for ARI prevail in rural setup [48]. However, in other studies [23,49], the residence was not significantly associated and Kumar et' al reported urban residence to be a risk factor for ARI [17].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors predispose children under five years of age for ARIs. These factors may be attributed to child factors such as age [11][12][13][14][15] and female sex [16], maternal factors such as lower age [11,13], unemployment [11,13] and lower educational status [16,17] environmental-related factors such as urban residence [17], rural residence [18], wet season [19][20][21] and co-morbid diseases [14,22,23]. There is a paucity of studies regarding the prevalence and associated factors of ARI among hospitalized under-five years children in Ethiopia even though few community-based cross-sectional studies [24][25][26] have been undertaken in to assess the prevalence and associated factors of ARIs among under-five years children.…”
Section: Introductionmentioning
confidence: 99%
“…The potential confounders were selected based on previously published studies [10,13,15,26,34,35] and data availability. Potential confounding factors were broadly classified into socioeconomic, demographic and behavioural, health service and community-level factors.…”
Section: Potential Confoundersmentioning
confidence: 99%